Challenges Facing the Implementation of Business Education CCMAS Curriculum in Public Universities - Nwatalari, Chinwe Nene; Onyemaobi, Ngozi; Odogwu, Ikechukwu Chidiebere (Journal of Research in Industrial Technology and Educational Studies, 2025)
The study looked into the problems of implementing Core Curriculum Minimum Academic Standards (CCMAS) in business and entrepreneurship education programs at public institutions. The research was guided by three research questions and three hypotheses. The population of the study comprised 133 participants: 30 business educators and 103 students from three public universities in South-East, Nigeria. The study utilized the complete population as the sample. Data were collected using a validated and reliable structured questionnaire. A four-point response options questionnaire was used for data collection, and it was validated by three experts. The instruments were administered by the researchers and research assistants. Responses to the research question was analyzed using mean responses, standard deviation while the hypotheses were analyzed using t-test of independent sample at 0.05 level of significant. Mean and standard deviation were utilized to answer the three study questions and evaluate the dispersion in respondents’ viewpoints, while one way analysis of variance (ANOVA) was employed to test the three null hypotheses at a significance level of 0.05. Findings show that; inadequate instructional facilities, inadequate funding, inadequate supply of technical manpower and qualified staff, technological advancement, and a large class of business education students are the challenges facing the CCMAS implementation in business education and entrepreneurship education programmes at public universities. To ensure effective CCMAS curriculum delivery, the study proposed additional financing, updated facilities, and expanded lecturers’ training.